Staphylococcal cassette chroromosome mec (SCCmec) typing of methicillin-resistant Staphylococcus aureus (MRSA) isolates from patients attending Tengku Ampuan Afzan Hospital (HTAA) in Kuantan, Pahang, Malaysia - Alarosi, Nasreen Mohammad (Kulliyyah of Medicine, International Islamic University Malaysia, 2011)
Staphylococcus aureus is a major human pathogen. It causes a wide range of infections in the hospital setting as well as in the community environment. A broad variety of infections, ranging from minor pyodermas to life-threatening infections can be caused by S. aureus.The adaptive power of S. aureus to antibiotics lead to the emergence of methicillin-resistant S. aureus (MRSA) in the early 1960s. The cause of resistance to methicillin is the acquisition of the mecA gene, which is situated on a mobile genetic element, the staphylococcal cassette chromosome mec (SCCmec). Five major variants of SCCmec, types I to V, are distinguished. One of the most important techniques used to investigate the molecular epidemiology of S. aureus is SCCmec typing. This technique has been used to study the evolution of the MRSA and to study their subsequent worldwide dissemination.This study was conducted to determine the molecular typing of methicillin-resistant S.aureus (MRSA) organisms isolated by the Bacteriology Laboratory in Hospital TengkuAmpuanAfzan (HTAA), Kuantan, Pahang, Malaysia from inpatients admitted during the period from 1stApril to 30th September, 2010. A total of 28 MRSA isolates were re-identified by known bacteriological methods and the minimal inhibitory concentration (MIC) of oxacillin was determined by E-test. The antibiotic susceptibility was tested, by disc diffusion method to 7 different antibiotics as recommended by the National Committee for Clinical Laboratory Standards (NCCLS).Resistance to oxacillin was 100%,erythromycin 82.1%, gentamicin75%, tetracycline 78.6%, and trimethoprimsulfamethoxazole78.6%. None of the isolates was resistant to vancomycin or chloramphenicol. All isolates showed an MIC >4μg/mL. All 28 MRSA isolates were subjected to SCCmec typing by duplex real time PCR, 78.5%(22/28) were shown to possess SCCmec-III and 21.5% (6/28) were of type IV. This confirms observations in several other neighboring Far Eastern countries and corroborates the epidemicity of this type in Kuantan, Malaysia.This work represents a valuable foundation study for future work on the antibiotic susceptibility/resistance profile and the epidemiology of MRSA SCCmec types in Kuantan, Malaysia.